PRODUCTION OF EXOPOLYSACCHARIDE AND POLYHYDROXYBUTYRATE BY NEWLY ISOLATED BACILLUS AP03 FROM INDUSTRIAL EFFLUENTS - CHAITANYA K; NAGAMANI.P; SK.MAHMOOD (International Journal of Pharma and Bio Sciences, 2013)
An exopolysacharide (EPS) along with internal granules of polyhydroxybutyrate (PHB) producing bacterium Bacillus sp AP 03 was isolated and identified from the industrial effluents. It was motile,aerobic, Gram positive, rod shaped, endospore forming and catalase producing bacterium. The isolated organism produced exopolymer and PHB in E2 medium consisting of glucose, nitrogenous substances. IR and GC spectra confirmed the presence of PHB and HPLC analysis confirmed the presence of EPS. Optimum conditions for polymer production were determined. Antimicrobial activities were also studied.16S rRNA analysis revealed that isolate AP03 had 99 % identity to Bacillus cereus and shared many similarities in terms of biochemical reactions and microscopic observations. The sequence of the 16S rDNA gene of strain AP 03 was determined (1341 bp) and deposited in the Gene bank sequence database under accession no. FN663621.